Evaluation of thermal and solar performance in atrium buildings using sequential simulation - Ab Ghafar, Norafida; Gadi, Mohamed; Adam, Mastura (SAGE Publications, 2019)
Nowadays complex atrium design is becoming popular in city skylines that bring natural lighting to create more pleasant indoor environment. Atriums with complex skylight design and lack of knowledge in building thermal performance in relation to transmitted solar radiation through skylight contribute to greenhouse effect. This has imposed high-energy consumption for cooling load particularly in warm humid regions. In order to obtain good thermal performance of atrium with appropriate skylight design, scholars in atrium studies have suggested that designers should test, simulate and evaluate the thermal performance of atrium building at the early design stage. This paper aims to investigate thermal and solar performance of atrium skylight design in warm humid region. Three thermal analysis software with different capabilities in evaluating thermal and solar performance of skylight forms, positioning and orientation were utilized. Five types of atrium design were modelled and simulated using Ecotect, EnergyPlus and solar radiation simulation model. The results have revealed that different software has different capabilities in measuring thermal and solar performance in atrium skylight design. Each software was used sequentially to provide results in stages starting from verifying variables, identifying critical climatic regions, measuring initial and validating accurate energy use for heating and cooling load until amount of solar received on atrium roof surface, geometry and curvature been achieved. This research could guide designers and engineers to understand the capabilities and reliability of selected thermal and solar analysis software in simulating and evaluating atrium’s thermal and solar performance at early stage design in order to identify appropriate low energy atrium design. © The Author(s) 2019.